Levodopa/Benserazide Loaded Microspheres Alleviate L-dopa Induced Dyskinesia through Preventing the Over-Expression of D1R/Shp-2/ERK1/2 Signaling Pathway in a Rat Model of Parkinson's Disease - Wan, Ying; Wu, Na; Song, Lu; Wang, Xijin; Liu, Zhenguo; Yuan, Weien; Gan, Jing (Frontiers in Aging Neuroscience, 2017)
Background: The long-term intermittent Levodopa (L-dopa) stimulation contributes to an aberrant activation of D1 receptor (D1R) mediated extracellular signal-regulated kinases1/2 (ERK1/2) in the striatal medium spiny neurons, resulting in the occurrence of L-dopa induced dyskinesia (LID). Recently, a novel signaling pathway, D1R/Shp-2/ERK1/2, was proposed to be required for the occurrence of LID. Here we designed the study in which two different methods of L-dopa delivery (continuous dopamine stimulation (CDS) versus intermittent dopamine stimulation) were used to further identify:1) the role of D1R/Shp-2/ERK1/2 signaling pathway in the occurrence of LID; 2) whether CDS alleviated LID though preventing the over-expression of the D1R/Shp-2/ERK1/2 signaling pathway. Methods: 6-OHDA-lesioned rat models of Parkinson’s disease (PD) were randomly divided into two groups to receive intermittent L-dopa stimulation (L-dopa/benserazide standard group, LS group) or CDS (L-dopa/benserazide loaded microspheres, LBM group) for 21 days. Dyskinesia and anti-parkinsonian effect were compared between the two groups through the AIMs assessment and cylinder test. The critical protein changes in the D1R/Shp-2/ERK1/2 signaling pathway were compared between the two groups through Western blotting. Results: Intermittent L-dopa administration induced serious dyskinetic movements in the 6-OHDA-lesioned rats, and the anti-parkinsonian effect of L-dopa was gradually counteracted by the occurrence of dyskinesia. Intermittent L-dopa administration enhanced the expression of membrane D1R, and induced a robust increase of phosphorylation of Shp-2, Src, DARPP-32 and ERK1/2 in the 6-OHDA-lesioned striatum. In contrast, CDS played a dose-dependent anti-parkinsonian role, without inducing such apparent dyskinetic movements. Moreover, CDS induced no change of membrane D1R expression or phosphorylation of Shp-2, Src, DARPP-32 and ERK1/2 in the 6-OHDA-lesioned striatum. Conclusion: The aberrant activation of D1R/Shp-2 complex was evidenced to be required for the D1R mediating ERK1/2 phosphorylation and the occurrence of LID. CDS effectively prevented the overexpression of D1R/Shp-2/ ERK1/2 signaling pathway, resulting in the reduction of LID in 6-OHDA-lesioned rats model of PD.